A miniature room temperature formaldehyde sensor with high sensitivity and selectivity using CdSO4 modified ZnO nanoparticles. Issue 92 (8th October 2015) - Chang, Xinghua; Peng, Mi; Yang, Junfeng; Wang, Teng; liu, Yu; Zheng, Jie; Li, Xingguo
<x xml:space="preserve">Abstract</x> A light activated miniature formaldehyde sensor working at room temperature is fabricated by CdSO4 modified ZnO nanoparticles.